RANCANGAN USULAN PERBAIKAN KUALITAS AKSESORIS KULKAS PADA BAGIAN INJECTION MOLDING DENGAN METODOLOGI SIX SIGMA DI PT HARTONO ISTANA TEKNOLOGI - MEILYANA, ANDITA
PT Hartono Istana Teknologi (HIT) or known as Polytron produces refrigerator with percentages 23.2% based on sales data in June 2018. To increase the competitiveness and maintain the level of customer satisfaction, the productivity and quality of products are being the focus of the company. However, Injection Molding Department has quality problems in produces refrigerator accessories. Two products accessories i.e Accessories BP-03 and Accessories EP-05 with a defect rate of 4% and 7% respectively. Therefore, the objective of this study is to increase the amount of production output by reducing the number of defective products by using Six Sigma methodology with DMAIC Approach (Define, Measure, Analyze, Improve, and Control). In the define phase, the Six Sigma project implementation is set in Injection Molding Department. In the measure phase, the results of the production process stability and process capability are obtained, with sigma value of 2.7514 for Accessories BP-03 and production utilities of 75.6410%, then 2.7018 for Accessories EP-05 with production utilities of 88.2716%. In the analyze stage, by using pareto chart and other considerations are found 4 types of defects, that are silver streaks, over stamping, scratch, and bubble. Delphi Method also used to identify factors and sub-factors that cause defects which are then made on Cause and Effect Diagram. These results are selected using the FMEA Method and obtained 5 causes with the highest RPN for each type of defect, i.e (1) the hopper was not functioning properly, (2) the design of the jig on the rubber was not good, (3) the standard for the additional jig design was not available, (4) the size of the place of the finished products was not suitable, and (5) the setting process used a setter’s analysis. In the improve phase, 5 alternative solutions are accepted by the company, i.e (1) checking the hopper condition by Maintenance Field, (2) evaluating the condition of the jig on the rubber, (3) designing the additional jig on the stamping machine, (4) designing the place of the finished products, and (5) evaluating the SOP of injection machine. In the control stage, work instructions and the implementation timeline are designed to guarantee the implementation of the proposed alternative solutions. From these researches, we expect benefits for the company i.e to reduce the number of defective products and increase production capacity for Accessories BP-03 and EP-05 in the Injection Molding Department.